Analisis Literasi Digital Mahasiswa Tahun Pertama Tadris Biologi - Nur Afinni, Ummi; Riris, Dinda; Armanda, Dicky; Fitri, Uci (Comit: Communication, Information and Technology Journal, 2024)
Digital literacy refers to an individual's ability to use digital technology with good understanding, including skills in finding, evaluating, using and sharing information effectively. This research was conducted to find out the history of the digital literacy level of first year students of Biology. To find out how the first year Tadris Biology students are able to access, understand, and evaluate scientific information that is relevant to the study of biology using digital technology. This study used a qualitative method using in-depth interviews via online, namely Google Meet. The importance of knowing or understanding digital literacy aims at good digital literacy skills that will assist students in accessing, understanding, and evaluating scientific information that is relevant to the study of biology. Keywords: digital literacy, digital technology, abilities